Criterion Variability in Binary Periscope Observation Decisions. (September 2017) - Ralph, Jason; Gabriel, Joseph; O'Donnell, Staci
Submarine control interfaces are developed with the assumption that the most important sources of variability are system and environment related. This study attempts to investigate the contribution of human sources of variability not related to the system or environment. In particular, this work focuses on criterion variability in initial contact decisions. Consistent with our understanding of signal detection theory as it relates to human decision making, we found significant variability in decisions caused by differences in response criterion/bias. We also found that the likelihood that stimuli matched a participant's direction of bias affected their decisions in the direction of their criterion/bias. The results indicate the importance of criterion variability as a measured parameter for decisions requiring levels of situational awareness beyond simple detection.